INTEGRAL ASSESSMENT AND MAPPING OF NATURAL DISASTERS RISK IN THE MARZES OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
From the point of view of natural disasters risk, Armenia is a vulnerable country. Therefore, the study and qualitative assessment of natural disasters is important for sustainable development of the Republic. The impact of natural disasters is directly linked to the feature of economy and population of the Marzes. For this reason, the study and qualitative assessment of natural disasters on the level of districts and regions has an important strategic significance. Risk is the probability of natural disasters, the assessment of which is based on their potential danger and vulnerability. On the basis of their potential danger and vulnerability, the risk of natural disasters on the territory of Armenia has been estimated and composed the integrated risk map.
Keywords: natural disaster; potential danger; vulnerability; risk assessment; community; frequency; risk